Determination of contrast medium dose for hepatic CT enhancement with improved body size dependency using a non-linear analysis based on pharmacokinetic principles. Issue 3 (March 2020) - Hibino, T.; Ichikawa, K.; Fang, Y.; Ito, S.; Kawashima, H.; Bae, K.T.
Abstract : AIM: To propose a pharmacokinetic non-linear analysis method to determine contrast medium (CM) dose for computed tomography (CT) hepatic enhancement to improve body size dependency and validate the proposed CM dose determination method through a clinical study. MATERIALS AND METHODS: Enhancement data of 105 patients who underwent hepatic dynamic CT with a fixed CM dose were analysed. From the analysis results, CM doses as a function of each of four body size indices (body weight [BW], lean body weight [LBW], blood volume [BV], and body surface area [BSA]) for achieving improved body size dependency were determined (proposed method), and the body size dependencies were simulated using the enhancement data from 105 patients. The proposed method was validated with a two-arm clinical study on BW. Body size dependency was evaluated using p -value of correlation coefficient between Body size indices and enhancements ( p< 0.05: significant dependency) and mean absolute error (MAE). RESULTS: The simulation showed that significant body size dependencies not considered by the conventional method can be improved by the proposed method. MAEs of BW, LBW, and BV were also significantly reduced ( p< 0.05). The clinical study with BW demonstrated a similar improvement to that in the simulation result. MAE was also significantly reduced ( p< 0.001). CONCLUSION: The proposed method demonstrated more improved BW, LBW, and BV dependence compared to the conventional method. Through the two-arm clinical study, the proposed method using BW only, without height information, is a suitable index for improving body size dependency. Highlights: Pharmacokinetic non-linear analysis is consistent with the contrast medium principle The exact CT contrast medium dose can be determined based on this analysis. The dose determination function includes a linear coefficient and a bias (intercept). Patient size dependency of hepatic enhancement is improved by the determined dose.